Using the Debate Method for Teaching Argumentation to 10-12 Year-Old Children - Y. V. Rybka (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to peculiarities of using the debate method in teaching argumentation to 10-12 year-old children. The research is aimed at identifying the most effective ways and means of applying the given method. According to the author's hypothesis, regular integration of discussions into the training course of rhetoric should promote learners' argumentation, changing it from a mere fantasy through egocentric attitudes to the objective position expressed in a conclusive argumentative way. To achieve the research objectives, the experimental training method was developed applying the debate technique in the form of role plays adapted to peculiarities of children's age. The experimental results indicated the decentration dynamics in the training process and, therefore, the effectiveness of the experimental training course. The presented training program can be used in teaching rhetoric to 10-12 year- olds, as well as in the optional argumentation course based on the debate technique. In addition, the analysis of children's argumentation position in the context of socio-cognitive approach can give an impetus for further studies of children's speech and thinking.